2023
DOI: 10.3389/fphar.2023.1131479
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling combined with network analysis of serum pharmacochemistry to reveal the therapeutic mechanism of Ardisiae Japonicae Herba against acute lung injury

Abstract: Introduction: Acute lung injury (ALI) is a common and devastating respiratory disease associated with uncontrolled inflammatory response and transepithelial neutrophil migration. In recent years, a growing number of studies have found that Ardisiae Japonicae Herba (AJH) has a favorable anti-inflammatory effect. However, its serum material basis and molecular mechanism are still unknown in ALI treatment. In this study, metabolomics and network analysis of serum pharmacochemistry were used to explore the therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The serum pharmacochemistry of TCM was designed to screen the efficacy material base of TCMs from the constituents absorbed into the blood after oral administration [ 33 , 34 ]. Thus the hypothesis suggests that the pharmacodynamic components of AJH, including bergenin, quercetin, epigallocatechingallate, rutin, cianidanol, myricitrin, ethyl gallate, kaempferol, taxifolin, cynaroside, myricetin, fraxetin, astilbin, and 13 other components ( Figure 10 ), may have an effect when combined with serum medicinal chemistry [ 18 ]. However, further research is needed to determine the specific mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum pharmacochemistry of TCM was designed to screen the efficacy material base of TCMs from the constituents absorbed into the blood after oral administration [ 33 , 34 ]. Thus the hypothesis suggests that the pharmacodynamic components of AJH, including bergenin, quercetin, epigallocatechingallate, rutin, cianidanol, myricitrin, ethyl gallate, kaempferol, taxifolin, cynaroside, myricetin, fraxetin, astilbin, and 13 other components ( Figure 10 ), may have an effect when combined with serum medicinal chemistry [ 18 ]. However, further research is needed to determine the specific mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that AJH exhibited significant anti-inflammatory properties and provided protection against LPS-induced ALI in rats. They found that the therapeutic effect of AJH on ALI was related to regulating the AGE-RAGE, PI3K-AKT, and JAK-STAT signaling pathways [ 18 ]. However, the specific pharmacodynamic components of AJH remain unclear, necessitating further investigation.…”
Section: Introductionmentioning
confidence: 99%